THE ROLE OF INFORMATION TECHNOLOGY IN THE DEVELOPMENT OF COMPUTERIZED AUDIT - Dewi, Adelia Riana (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
Accounting and Information Technology (IT) and Information Systems have become intertwined in the world of education. The rapid development of Information Technology has also resulted in significant accounting changes. The utilization of Information Technology as a supporter of the achievement of organizational goals and objectives must be balanced with the effectiveness and efficiency of its management. The rapid development of Information Technology has also resulted in significant accounting changes. At each step of accounting's evolution, information technology plays a distinct function. The more sophisticated Information Technology is, the greater impact it has on the accounting profession. This research will be carried out to see the role of information technology in developments in computerized auditing. This research was carried out using a qualitative literature study method. This study found that advances in information technology can provide new opportunities for the accounting profession. The new opportunities include computer-based information system consultants, CISA, and web trust audits.